Short communication: Upregulation of hypoxia/reoxygenation-induced Shc3 by downregulated miR-455-5p, suppresses trophoblast invasion and is associated with placental inflammation and angiogenesis in preeclampsia. - Hui-Zhi Gong; Jing Guan; Ying-Zi Pan; Hong-Juan Ding; Ai-Wu Shi; Ning Gu (PLoS ONE)
Preeclampsia is characterized by insufficient invasion of extravillous trophoblasts and is a consequence of failed adaption of extravillous trophoblasts to changes in the intrauterine environment developing embryo. Specific miRNAs are implicated in the development of preeclampsia (PE). miR-455-5p is present at low levels in PE but its role is not known. Combining cell and molecular biology methods, we provide evidence of the function and mechanism of miR-455-5p action, and identify its potential target, Shc3, in PE. In vitro, when miR-455-5p was overexpressed in HTR-8/SVneo cells they migrated and invaded more rapidly under hypoxia/reoxygenation (H/R) than in either hypoxic or normoxic conditions. In contrast, apoptosis of HTR-8/SVneo was reduced in H/R. Shc3 was identified as a direct downstream target gene of miR-455-5p. Overexpression of Shc3 reversed the effect of miR-455-5p, promoting apoptosis and suppressing invasion and migration of HTR-8/SVneo under H/R. Shc3 was highly expressed in H/R, but its level was reduced in isolated hypoxic or normoxic environments. Furthermore, we showed Shc3 overexpression is involved in placental inflammation and angiogenesis inhibition. Finally, we showed that the downregulation of miR-455-5p in PE contributes to increased Shc3 in extravillous trophoblasts, thereby limiting extravillous trophoblast cell invasion. Elevated Shc3 is associated with placental inflammation and angiogenesis inhibition. Thus Shc3 serves as a potential biomarker for PE diagnosis and treatment.